If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -15 = 7x + -60 Reorder the terms: -15 + 4x = 7x + -60 Reorder the terms: -15 + 4x = -60 + 7x Solving -15 + 4x = -60 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -15 + 4x + -7x = -60 + 7x + -7x Combine like terms: 4x + -7x = -3x -15 + -3x = -60 + 7x + -7x Combine like terms: 7x + -7x = 0 -15 + -3x = -60 + 0 -15 + -3x = -60 Add '15' to each side of the equation. -15 + 15 + -3x = -60 + 15 Combine like terms: -15 + 15 = 0 0 + -3x = -60 + 15 -3x = -60 + 15 Combine like terms: -60 + 15 = -45 -3x = -45 Divide each side by '-3'. x = 15 Simplifying x = 15
| (7x+15)=8x | | 2(x-4)=35 | | 3/r=12/17 | | y=(7+5k)x | | 4x^2+28x^3=0 | | 3k-5=7k+7 | | 2a+9=22249 | | 4x-31+2x=11 | | ln(3.2)=x | | 2(c+6)=c-13 | | 7y-8+6y+1= | | 13x+8-10x=65 | | x/-6=1-(-4) | | 4x+y+2xy+6y-2x= | | logx(3x-1)=0 | | 7/2=91/x | | 6-y=-y+2 | | (xy)dx=(1+x^2)dy | | 12-6r=2r+36 | | 12-5=x/4 | | 6x-15-x=65 | | 1/5x-9/10x=10-31 | | 10=s-2 | | 7+(3)= | | 9c=50f-160 | | 16x+11=6x+231 | | 29x-34x=7-12 | | (8x+18)+(20x+4)=(6x+4) | | -4n+2=-54 | | x^2+y^2+4x+4y+8=9 | | 48-11=35x+15 | | -39+18=-5x+12x |